The enigma of a keratitis-ichthyosis-deafness with silence, scaling, and related syndrome - Mariya Kharodawala; Shekhar N Pradhan; Anil Gosavi; Sunil Tolat (Wolters Kluwer Medknow Publications, 2023)
Ichthyosis is a group of genetic disorders characterized by generalized dry skin and scaling, and it can be frequently associated with erythroderma. Here, we report a case of ichthyosis associated with a rare syndrome. A 6-year-old congenitally deaf female presented with severe scaling and generalized erythema for 6 months which began with a scaly plaque over the face at the age of 18 months and gradually covered the whole body. Three similar episodes happened after that with a gap of 6 months. There were multiple scaly erythematous plaques present over the trunk and limbs and thick hyperkeratotic plaques were present in axillary and inguinal folds. The scalp hairs were sparse. Histopathology showed psoriasiform changes. Salivary sample sent for genetic analysis revealed an heterozygous mutation c.42C>G (p.Asn14Lys) in GJB2 gene that is known to harbor pathogenic mutations associated with keratitis-ichthyosis-deafness (KID) syndrome. KID syndrome presents with the triad of keratitis, progressive erythrokeratoderma, and hearing loss.